Pamela Anderson and Web 2.0: Adapting to change and changing the world, one tweet at a time - Raphael, Jackie (Black Swan Press, 2013)
The Hollywood entertainment industry and celebrity status have had a global impact on advertising and consumption since their emergence in the early twentieth century. However, the advent of the Internet and social media as means of mass communication has transformed both celebrity culture and the advertising industry. In this paper, a case study of Hollywood identity Pamela Anderson illustrates the changes that have occurred in how a celebrity brand can be initiated and maintained. The complex interaction of celebrity identity, choice of endorsement and control of access to the means of publication are also examined. This relationship is investigated in terms of social media statistics, semiotic analysis of online branding, the application of Grant McCracken’s meaning transfer theory to endorsements, and interviews with industry professionals. It is concluded that Web 2.0 has transformed the nature of celebrity-fan interaction and consumer-advertiser communication, and is significantly shifting media control and censorship away from businesses and government towards celebrities and their audiences.